2013
DOI: 10.1159/000348721
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Based Cytology of the Breast: Pitfalls Unrecognized before Specific Liquid-Based Cytology Training - Proposal for a Modification of the Diagnostic Criteria

Abstract: Objectives: To describe the pitfalls encountered in switching over from conventional smears (CSm) to liquid-based cytology (LBC). To explore modifications of our usual diagnostic criteria. Study Design: 190 ThinPrep breast samples with paired biopsies were retrospectively evaluated by two breast cytopathologists experienced only in CSm. They were again studied after LBC training. The diagnostic performances were compared. In additional calculations we included those C4/suspicious samples containing 70% high-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…4,6,17,18 On the other hand, alterations in architecture and cellular morphology as well as loss of informative background are usually seen in FNA smears prepared by LBC. 16,17,19,20,21 In the present study, the age range and mean age was comparable with other studies. 4,16,19 In our study 53% of tumours were located in the right breast whereas 47% of tumours were located in the left breast which was similar to the findings of Ryu HS et al 16 In the present study we compared 100 MLBC and conventional FNA smears on following Cytomorphological parameters:-…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…4,6,17,18 On the other hand, alterations in architecture and cellular morphology as well as loss of informative background are usually seen in FNA smears prepared by LBC. 16,17,19,20,21 In the present study, the age range and mean age was comparable with other studies. 4,16,19 In our study 53% of tumours were located in the right breast whereas 47% of tumours were located in the left breast which was similar to the findings of Ryu HS et al 16 In the present study we compared 100 MLBC and conventional FNA smears on following Cytomorphological parameters:-…”
Section: Discussionsupporting
confidence: 90%
“…Most of the smears showed better-preserved cells with enhanced nuclear detail, including a more pronounced nucleoli which was also observed by various other authors. 6,16,17 Thus Micheal CW et al, 17 Biscotti CV et al 21 and Feoli F et al 20 observed that in order to avoid diagnostic errors it is advisable to undergo prior training in LBC to understand the morphological changes produced by LBC. Most of the MLBC smears showed cells arranged in monolayered sheets that enabled us to study the cell morphology even better which was also observed by Pawar PS et al 24 In the present study that there was an apparent decrease in number of myoepithelial cells in MLBC smears as compared to CS which was also observed by other authors.…”
Section: Cell Changesmentioning
confidence: 99%
“…These results lie within the range published in the literature. We would just like to offer some comments based also on our recent experience with liquid-based cytology (LBC) samples [7]. We hope that they could eventually help our Australian colleagues to further improve their accuracy.…”
mentioning
confidence: 99%
“…In these settings, LBC avoids air-drying, spreading artifacts and the obscuring effects of blood and inflammation. Using LBC we have recently observed only 4% of inadequate samples [7]. With conventional smears, our inadequate rate has been 14.04% [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation